If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3u + -1 = -7 Reorder the terms: -1 + -3u = -7 Solving -1 + -3u = -7 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3u = -7 + 1 Combine like terms: -1 + 1 = 0 0 + -3u = -7 + 1 -3u = -7 + 1 Combine like terms: -7 + 1 = -6 -3u = -6 Divide each side by '-3'. u = 2 Simplifying u = 2
| 0=x^3-6x^2+12x-3 | | 30-x=10 | | 17b+-15b+5=-7 | | 18k^2=36k | | x^4+5x^2=14 | | 5k+6k-6k-3=17 | | 35-2s=11 | | 3(a-4)-2(a+4)=6 | | X+4x=245 | | 5y-8a+6xy-7x= | | 0.32x+0.48=1.44 | | 3d+1=6d-3 | | -2x^2-2x+24=0 | | -3x+4=3x-20 | | 4x^2-5x+13=7x+8 | | -4(35)(45)+7= | | x=-2+-4y | | 30-12x=-60-14x | | 81+b^2=225 | | -4x^3-48x^2-80x=0 | | x^2-2x+11=5x+1 | | 1=x/7-3 | | -5=x/15+3 | | 5-3(x-2)+x=23 | | -56-5x=-2x+37 | | 4x_-7=5-2x | | -2+x/26=-6 | | x^2+x-4=2 | | -56-14x=59-19x | | 2.68*25= | | 1y+8= | | -7-2=11-8x |